Analisis Kualitas Perairan Pada Wilayah Perairan Pulau Serangan Bagian Utara Berdasarkan Baku Mutu Air Laut - Saraswati, Ni Luh Gede Rai Ayu; Arthana, I Wayan; Hendrawan, I Gede (Journal of Marine and Aquatic Sciences, 2017)
Water quality monitoring is one of important activity, especially in coastal water, which susceptive with pollution. Water area of Serangan Island is a tidal flat area, influenced by fresh water and sea water inputs. The existence activities, such as cage aquaculture and tourism, and input from river, are threatened to decrease the water quality in north of Serangan water. This research was conducted to the condition of water quality based on water quality standard for aquatic organisms and its spatial distribution. The parameters measured were temperature, salinity, pH, DO, turbidity, and BOD 5 , in 8 sample points. Some parameters measured directly on water surface (temperature, salinity, pH and DO) and the others were analyzed in laboratory (turbidity, and BOD 5 ). BOD 5 was analyzed by standard method of Delzer & McKenzie. Based on research, the result of temperature values ranged from 28,9°C-30,5°C; salinity 29,6 ppt-32,7 ppt; pH 7,7-7,9; DO 3 mg/L-4,4 mg/L; turbidity 1,9 ntu-7,6 ntu; and BOD 5 2,8 mg/L-5,4 mg/L. The water quality in Serangan had a different spatial distribution in each parameters. Overall, based on research result, the water quality condition in the body water of Serangan island was good and suitable to support aquatic organisms living.